The Meaning and Symbols of Offerings in the Karo Ritual Ceremony of the Tengger Tribe in Baledono Village - Nafridhatul Maulidina Wardani; Kukuh Sinduwiatmo (Universitas Lambung Mangkurat, 2025)
This study was conducted to analyze the symbolic meaning contained in the offerings in the Karo Ceremony ritual carried out by the Tengger Tribe in Baledono Village. The rituals and offerings used in this ceremony are not only part of the traditional procession, but also have meanings that reflect the spiritual, cultural, and social relationships of the Tengger community. This study uses a qualitative type with a descriptive approach. The subject of this study is the meaning and symbols of the offerings. While the research subjects were selected by purposive sampling. The object is the Karo ceremony of the Tengger Tribe in Baledono Village. Data collection techniques to obtain information through observation, in-depth interviews, and documentation. Then analyzed using descriptive interpretive data analysis techniques. The results of the study explain that each symbol in the offerings has a deep meaning that is closely related to the six indicators of F.W. Dillistone's symbol theory. It is important to understand this symbolic meaning so that the preservation of the culture and traditions of the Tengger Tribe is maintained amidst the dynamics of the ever-changing era.